Community perspective and challenges of heritage buildings conservation in urban Malaysia - Marmaya, Ezyana Anyzah; Mahbub, Rohana; Muhammad, Faudzi; Mohd Tahir, Mas Ayu (UiTM Press, 2025)
Understanding the significance of Malaysia's heritage buildings, especially in areas such as Kuala Lumpur and Penang, is essential for several reasons. Kuala Lumpur and Penang, a region renowned for its rich architectural and cultural legacy, is the location of various structures that illustrate the city's historical development from the British colonial era to the dynamic, multicultural present. These heritage buildings could become cost-effective investments that benefit ancillary economic growth in local or regional areas. This paper aims to review the Malaysian public's concern about heritage building conservation, including identifying key reasons and challenges for retaining these buildings in Kuala Lumpur and Georgetown Penang. Both locations, which were designated as World Heritage Sites, are renowned for having a large number of historically significant structures that are older than 100 years. However, not all historic structures have been suitably preserved in the neighbourhood, particularly by the owners and tenants. Due to this, there are severe problems with heritage buildings that need to be addressed by the public and their owners. The research method adopted was the quantitative approach employing a questionnaire survey with 100 questionnaires distributed to local respondents. From the community's observation, heritage buildings in Georgetown needed to be adequately conserved compared to Kuala Lumpur. In addition, the study findings conclude that the locals' degree of knowledge in both locations is fairly excellent.